Intra-Abdominal Pressure Monitoring by Surface Bioimpedance Estimation. (July 2019) - David, M; Yellin, E; Pracca, F; Simini, F
Abstract: Intra-abdominal hypertension (IAH) is produced by an accumulation of liquids in the abdominal cavity. In such case, the intra-abdominal pressure (IAP) increases, and the abdominal wall is stretched. Previously, an inverse correlation between the abdominal wall's thickness and the IAP was theorized. Since the abdominal wall can be modelled as a compound of parallel dielectric slabs, changes in their width have direct effect on its overall bioimpedance. Numerical analyses of the bioimpedance as a function of the compression of the abdominal wall were verified by an in-situ trial on a porcine model. In this work, we present the project of a medical grade bioimpedance spectroscopy system along with a summary of our findings.